HUBUNGAN NETRALISASI TERHADAP SIFAT FISIKO KIMIA PADA LEMAK BIJI TENGKAWANG - Haryanti, Wiwik Dwi (Jurnal Pembelajaran Prospektif, 2018)
There are more than 13 species of Tengkawang tree in Indonesia, mainly grown in Kalimantan and a few in Sumatera. Tengkawang species of a valuable tengkawang kernel that up to now just harvested from the natural forest. At the end of kernel production period, the trees can be cut to produce valuable timber for playwood and sawn timber industries. In this study, Tengkawang kernel was extracted by soxhlet extraction apparatus using petroleum ether as solvent. The extraction yields a yellow fat and after the process of purification/neutralization conducted, it was found the acid number 14.32 decrease to 10.22, free fatty acids 7.196% decrease to 5.14%, saponification 198.23 mgKOH/gram sample decrease to 178.23 mgKOH/gram samples, peroxide number mgO2 4.91/100g sample to 3.24 mgO2/100g samples and materials do not saponified 1.13% decrease to 1.12%, and the yield on solvent extraction with 43.50%.